Information acquisition in conflicts - Florian Morath; Johannes Münster (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
This paper considers incentives for information acquisition ahead of conflicts. First, we characterize the (unique) equilibrium of the all-pay auction between two players with one-sided asymmetric information where one player has private information about his valuation. Then, we use ou rresults to study information acquisition prior to an all-pay auction. If the decision to acquire information is observable, but not the informatio nreceived, one-sided asymmetric information can occur endogenously in equilibrium. Moreover, the cutoff values of the cost of information that determine equilibrium information acquisition are higher than in the first best. Thus, information acquisition is excessive. Incontrast, with open or covert information acquisition, the equilibrium cut-off values are as in the first best.
urn:nbn:de:bvb:19-epub-13240-2
Keywords: D72; D74; D82; D83; 330; All-pay auctions; Conflicts; Contests; Information acquisition; Konflikt; Informationsversorgung; Informationsverhalten; Auktionstheorie; Wettbewerb; Theorie